Tides during monsoon season in Peninsular Malaysia - Mahmud, Mohd. Razali; Tan, Tai Hung (2006)
Tide, a natural phenomenon with awesome characteristics, consists lots of mysterious and knowledge which acquire continuous research. With physical terrain that is surrounded with sea, Malaysia is a country where the determination of tidal prediction, mean sea level, chart datum are carried continuously through out the years. A software named μ-TAPS was developed for the tidal analysis and prediction. It successfully tells the characteristic of tides in Malaysia and the results achieved correspond with the Royal Malaysian Navy, and the Department of Survey and Mapping Malaysia’s tidal prediction. In this study, μ-TAPS is used for the tidal prediction process during monsoon season. Tidal data was gathered for few years to determine the tidal constituents. The focus of this study is year 2005 for the month of December at the southern part of Peninsular Malaysia. The rain falls data was gathered hourly during the period and it was the main factor effecting the tidal prediction through out the monsoon seasons. The tidal prediction was compared with the role data during the period, and the effect from rain fall’s volume was determined with some finding of correlation. The exceeding value from the prediction was compared with the normal tidal curve and the result would determine whether floods could occur at coastal area.